Sistem Informasi Data Kependudukan Berbasis Web Di Kantor Kecamatan Cikarang Timur - Agung Nugroho; Afif Mulyana (Jurnal SIGMA, 2018)
The development of information technology in the era of globalization has experienced rapid development. Along with the rapid advances in information technology. Information is a very important thing in carrying out a job and activity so that it can affect aspects of life. The purpose of this final project report is to study, analyze, and design a population system, which will be applied at the East Cikarang District office. Software that will be developed in the preparation of this final project uses the PHP (Personal Home Page) programming language and MySql as a database. The development of this information system is done by using the Waterfall model and the data flow method using a structured method where the design uses DFD (Data Flow Diagram). In the end, this system is expected to provide convenience for sub-district employees as well as residents, so that information can be received easily and quickly because the information system can facilitate input and search population data